2006
DOI: 10.1111/j.1742-4658.2006.05152.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural characterization of a mimetic membrane‐anchored prion protein

Abstract: During pathogenesis of transmissible spongiform encephalopathies (TSEs) an abnormal form (PrPSc) of the host encoded prion protein (PrPC) accumulates in insoluble fibrils and plaques. The two forms of PrP appear to have identical covalent structures, but differ in secondary and tertiary structure. Both PrPC and PrPSc have glycosylphospatidylinositol (GPI) anchors through which the protein is tethered to cell membranes. Membrane attachment has been suggested to play a role in the conversion of PrPC to PrPSc, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 71 publications
2
33
0
Order By: Relevance
“…Thus, the effect of membrane binding on the structure of PrP is naturally of interest. Recent studies used recPrP with synthetic membrane anchors and followed the secondary structure upon lipid contact by using either UV-CD spectroscopy (19) or FTIR measurements (20). Both studies concluded that the structure of recPrP, with a synthetic membrane anchor, is identical upon lipid contact to the structure of anchorless PrP in lipid-free solutions.…”
mentioning
confidence: 99%
“…Thus, the effect of membrane binding on the structure of PrP is naturally of interest. Recent studies used recPrP with synthetic membrane anchors and followed the secondary structure upon lipid contact by using either UV-CD spectroscopy (19) or FTIR measurements (20). Both studies concluded that the structure of recPrP, with a synthetic membrane anchor, is identical upon lipid contact to the structure of anchorless PrP in lipid-free solutions.…”
mentioning
confidence: 99%
“…Thus, generating membrane-anchored PrP using recombinant expression in combination with selective chemical modifications is a viable alternative, which has been used by several groups so far (9,20,21). Here, we utilize a strategy developed previously in our group that relies on expressed protein ligation to prepare PrP con-taining a C-terminal membrane anchor that mimics a GPI anchor and conveys strong membrane attachment (22).…”
mentioning
confidence: 99%
“…100,101,105,106 Beyond, the fluorescent protein GFP was also used to demonstrate the membrane anchoring properties of such synthetic lipids. 93,94,100,101,103,[105][106][107][108][109] It was found that the removal of the carbohydrate moiety or its truncation can retain the anchoring function of the GPIs.…”
Section: Synthetic Glycosylphosphatidylinositol Analoguesmentioning
confidence: 99%
“…97 Even though the membrane attachment seems to be crucial for the pathogenesis, previous studies have only been performed with recombinant, soluble PrP lacking any membrane anchor 98,99 or with PrP having anchor mimics structurally not related to the native GPI anchor. 93,94,100,101 The structural consequences of the membrane association of these PrP derivatives have not been investigated on cellular or model membranes.…”
Section: Prion Proteinmentioning
confidence: 99%
See 1 more Smart Citation